Forgery Of Deed Documents Between Indonesian And Dutch Law - Aurelya, Diaz; Santoso, Bambang; Aldyan, Arsyad (CV. Inara, 2024)
Mail forgery has a wide-ranging and serious impact, not only on the individual victims, but also on social stability, security, and trust in the legal system and government. Mail forgery can include various types of documents, ranging from personal documents such as identity cards and passports, to official documents such as certificates, deeds, and financial documents. This research is normative research that studies the purpose of law, values of justice, validity of legal rules, legal concepts, and legal norms. The source materials used in this research are primary legal materials, secondary legal materials and tertiary legal materials. Primary legal materials are the Indonesian Criminal Code and the Dutch Criminal Code. Furthermore, the data collected is analysed qualitatively. Indonesian law regulates related to the criminal offence of document forgery can be found in various laws. Among them are: Article 263 of the Criminal Code, Article 264 of the Criminal Code. In addition, Law Number 24 of 2013 concerning amendments to Law Number 23 of 2006 concerning population administration regulates the falsification of population documents such as KTP and birth certificates including deeds. As for the Dutch Legal Aspects, it specifically regulates Article 225 of the Dutch Criminal Code regarding forgery of all forms of documents that cause harm to others can be penalised and fined. The same as in Indonesia which regulates document forgery.